Malignant solid tumors in basra pediatric oncology center - J. Dawood, Lamya’a; G. Hasan, Janan; M. Salah, Hussam (Scientific Journal of Medical Science, 2015)
Malignant solid tumors represent about 50% of all malignant neoplasm in children aged less than 15 years ,They make more than 80% of all malignancies in infants. To focus on clinical and biological characteristics of patients with various types of malignant solid tumors who have been admitted to the Oncology center at Basra Maternity and Children Hospital during the period from the 1st of January 2004 till the end of December 2009. A retrospective study was carried out at Basra Maternity and Children Hospital during the period from the 1st of January 2004 till the end of December 2009.Total cases of cancer admitted to the Center during that period were 704 cases, malignant Solid tumors represented 27.5% of total cases(194 cases). One hundred sixty five patients were included in the study, their age ranged from one month to 14 years, 85 males and 80 females. Sympathetic nervous system tumors represented the highest percentage (35.8%) followed by renal tumors (26.1%), soft tissue sarcomas (18.2%), germ cell tumors (10.3%), retinoblastoma (6.7%) and the least percentage was for hepatic tumors (3%) . The highest frequency of malignant solid tumors was found in the age group of (1-4years), that included 79 patient (47.9%), most of them had neuroblastoma ;32 patients (40%). Most cases with malignant solid tumors were from the center and northern areas of Basra (28.5%,14.6% respectively) and to a lesser extent in western (10.3%), southern (6%), and eastern areas( 1.2%). Other governorates like ThiQar and Maysan account for high rates (21.8%,16.4% respectively) of admissions in Basra pediatric oncology center. The overall mortality was 27.3% (45 cases), it ranged from 11.8%-40%, and most common cause of death was advanced metastatic disease. Non compliance or discontinuation of treatment is an important dilemma for all types of cancer. This study revealed that sympathetic nervous system tumors, the commonest of them was neuroblastoma , most cases presented in stage III or stage IV of the disease. So Improving the diagnostic facilities in Basra Oncology Center by introducing specific type of investigation for evaluation of patient with malignant solid tumors like metaiodobenzylguanidine (MIBG) scan, positron emission tomography (PET), genetic study, and other important biochemical investigations could assign the patient risk group, and not depending only on simple criteria for the classification of the disease .